Effect of Zytron and Its Degradation Products on Soil Microorganisms - Fields, M. L. (1966)
There was no adverse effect of Zytron, o-2,4-dichlorophenyl o-methyl isopropyl phosphoramidothioate, a herbicide, upon molds, actinomycetes, and soil bacteria in field plots, or upon selected soil microorganisms in model systems. 2,4-Dichlorophenol, a degradation product, was found to be toxic at levels above 10 ppm to molds, but levels this high were not found in soil from treated plots. Aspergillus clavatus degraded both Zytron and 2,4-dichlorophenol. Sodium o-methyl isopropyl phosphoramidothioate, another degradation product of Zytron, stimulated the growth of a species of Penicillium.